Service Quality dan Campus Image: Strategi Meningkatkan Loyalitas Mahasiswa di Perguruan Tinggi - Yunita Iliana; Sabar; Bisma Jatmika Tisnasasmita (Value : Jurnal Manajemen dan Akuntansi, 2026)
Increasingly intense competition in higher education demands universities to attract new students and continuously build student loyalty. This study aims to analyze the influence of service quality and campus image on student satisfaction and loyalty, as well as to examine the mediating role of student satisfaction and the moderating role of competitive intensity in the student loyalty model. This study used a quantitative explanatory approach with a cross-sectional design involving 138 active students at private university X in Banyuwangi. Data were collected through structured questionnaires and analyzed using SEM-PLS. The results showed that service quality and campus image had positive and significant effects on student satisfaction. Campus image also had a direct effect on student loyalty, whereas service quality did not show a significant direct effect. Student satisfaction has been proven to have a positive effect on student loyalty, fully mediating the relationship between service quality and student loyalty, and partially mediating the relationship between campus image and student loyalty. Other findings indicate that competitive intensity weakens the influence of student satisfaction on loyalty. These results broaden the reading of Stimulus–Organism–Response (SOR) into the perspective of Environment–Stimulus–Organism–Response (E-SOR) by positioning competitive intensity as an environmental element that limits the strength of the relationship between satisfaction and loyalty.